Assessment on performance-properties of asymmetric nanofiltration membranes from polyethersulfone/n-methyl-2-pyrrolidone/water blends with poly(vinyl pyrrolidone) as additive - Rozali, S.; Safari, N. H. M.; Hassan, A. R.; Ahmad, M. S.; Yunus, R. M. (Budapest University of Technology and Economics, 2022)
In this study, the effect of poly(vinyl pyrrolidone) (PVP) additive on the fabrication of asymmetric nanofiltration (NF) membranes was investigated in terms of performance, structural details and key properties. On addition of PVP ranging from 2 to 10 wt% into the dope solution, the fabricated NF membranes exhibited significantly different in properties and improved performance. In particular, the membranes made from 2 wt% PVP had the highest water flux and salt rejection of about 3.61 × 10–6 m3/m2s and 44.49 %, respectively. Modeling results revealed that small amount of PVP (2–4 wt%) produced finer structural properties. Moreover, the key properties (rp, ∆x/Ak and ζ) of the fabricated NF membranes were found to be within the range of that of commercial NF membranes.